Malaysia's quest for innovation progress and lessons learned - Thiruchelvam, Kanagasundram; Chandran, V.G.R; Ng, Boon-Kwee; Wong, Chan-Yuan (Strategic Information and Research Development Centre, 2013)
This book provides an excellent overview on Malaysia's science, technology and innovation. It details the country's present STI landscape and sketches some of the key challenges the country will have to address in its ambition of becoming an innovation-driven economy by the end of the decade.